Developing Shared Appraisals of Diabetes Risk Through Family Health History Feedback: The Case of Mexican-Heritage Families - Lin, Jielu (Ann Behav Med, 2018)
BACKGROUND: Collecting complete and accurate family health history is critical to preventing type 2 diabetes. PURPOSE: We seek to identify the optimal risk feedback approach that facilitates risk communication between parents and their adult children and helps them develop shared appraisals of family history of type 2 diabetes. METHODS: In a sample of parent-adult child dyads from 125 Mexican-heritage families residing in Houston, Texas, we examine change in parent-child dyadic (dis)agreement with respect to their shared family health history from baseline to 10 months after receipt of risk feedback generated by Family Healthware. A 2 × 2 factorial design is applied to test how the recipient (one parent or all family members) and the content (risk assessment with or without behavioral recommendations) of the feedback affect (dis)agreement through interpersonal ties, particularly dyadic risk communication. RESULTS: Providing risk assessment without behavioral recommendations to the parent, but not the adult child, shifts the dyads toward agreement (relative risk ratio [RRR]= 1.78, 95% confidence interval [CI] [1.18–2.67]), by activating reciprocal risk communication between parents and children (RRR =2.70, 95% CI [1.81–4.03]). Dyads with close interpersonal ties are more likely to shift toward agreement (RRR = 3.09, 95% CI [1.89–5.07]). CONCLUSION: Programs aimed at improving family health history knowledge and accuracy of reports should tailor risk feedback strategically for better intervention effect and leverage a network approach in disease prevention among at-risk minority and/or immigrant populations. TRIAL REGISTRATION NUMBER: NCT00469339.